Old Ice, Ong Valley, Transantarctic Mountains - Bergelin, Marie; Putkonen, Jaakko (IEDA: US Antarctic Program Data Center, 2023)
These data include the measurements and analyses done on a ~10 meter long ice cores drilled in Ong Valley buried ice site. Further descriptions can be found in the related paper listed below.